The Impacts of Perceived Risk and Negative Emotions on the Service Recovery Effect for Online Travel Agencies: The Moderating Role of Corporate Reputation - Wei, Jiahua (Frontiers in Psychology, 2021)
This study explored the impact mechanism of perceived risk and negative emotions on the service recovery effect of online travel agency (OTA) through scenario experiment. The results show that: Perceived risk has a positive and negative impact on negative emotions and service recovery satisfaction, negative emotions have a negative impact on service recovery satisfaction, corporate reputation plays a positive moderating role in the relationship between perceived risk and service recovery satisfaction. This study is helpful to better explain the impact mechanism of service recovery effect of OTA, to provide a theoretical reference for improving the service recovery effect of OTA.